2014
DOI: 10.1200/jco.2013.53.5831
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Stage I Nonseminoma Testicular Cancer: Outcomes and Long-Term Follow-Up in a Population-Based Cohort

Abstract: A surveillance policy for patients with stage I NSGCC is a safe approach associated with an excellent cure rate and an overall low treatment burden despite a high relapse rate in a small group of patients. We recommend surveillance for patients with stage I NSGCC with immediate systemic treatment at relapse. Clearly defined risk factors for relapse are presented if an option of risk-adapted treatment is preferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
146
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(160 citation statements)
references
References 20 publications
8
146
0
3
Order By: Relevance
“…The rete testis invasion has also been associated with higher odds of recurrence (Fig. 7.41) [123,277,278]. In the same study by Warde et al, patients with tumor invading into the rete testis had a 1.7 higher risk of relapse.…”
Section: M0mentioning
confidence: 85%
See 1 more Smart Citation
“…The rete testis invasion has also been associated with higher odds of recurrence (Fig. 7.41) [123,277,278]. In the same study by Warde et al, patients with tumor invading into the rete testis had a 1.7 higher risk of relapse.…”
Section: M0mentioning
confidence: 85%
“…Lymphovascular invasion has been extensively demonstrated as a significant prognostic factor, particularly in nonseminomatous GCT (Fig. 7.40) [127,[275][276][277]. In pure seminomas, the association of lymphovascular invasion with relapse is less clear [122,123,126,278] N categories are based on the number of nodes involved and size of metastatic deposits, and M categories depend on whether there is metastatic deposits and, if so, if these involve nonregional nodes, lung, or any other site.…”
Section: Stagingmentioning
confidence: 99%
“…On the other hand, even if recurrences of germcell tumours of the testis are rare, most relapses in patients with germ-cell tumours occur within the first 2 years of treatment [14][15][16] , and no excess mortality has emerged in population-based studies 7,17 . Increasing survival is also expected for other cancer types as a result of personalized treatments based on a better understanding of the biology and potential response to therapies of each individual cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,4 Relapses beyond two years are considered late relapse and are much less common. A 2007 systematic review of testicular GCT surveillance found only seven reported recurrences after five years of surveillance, with a maximum time to relapse of 14.25 years.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, this approach has been recommended by several guidelines and adopted by many other centres worldwide. 1,[3][4][5] The current active surveillance protocol for CSI NSGCT at Princess Margaret involves regular and structured monitoring of tumour markers (alpha-fetoprotein [AFP], human chorionic gonadotropin [hCG], lactate dehydrogenase [LDH]) and computed tomography (CT) scans of the chest, abdomen, and pelvis, and has been previously outlined in the literature. 1,6 After two years of active surveillance, the intensity is tapered.…”
Section: Introductionmentioning
confidence: 99%